Therapeutic potential of omega-3 fatty acids supplementation in a mouse model of dry macular degeneration. Issue 1 (19th June 2017) - Prokopiou, Ekatherine; Kolovos, Panagiotis; Kalogerou, Maria; Neokleous, Anastasia; Papagregoriou, Gregory; Deltas, Constantinos; Malas, Stavros; Georgiou, Tassos
Abstract : Purpose: To evaluate the therapeutic effects of omega-3 (ω-3) and omega-6 (ω-6) fatty acids in the CCL2 −/− model of dry age-related macular degeneration (AMD). The blood level of eicosapentaenoic acid (EPA) and arachidonic acid (AA) served to adjust the treatment dosage (AA/EPA=1–1.5). Methods: Nine-month-old animals were allocated to different groups: (A) C57BL/6 untreated, (B) CCL2 −/− untreated, (C) CCL2 −/− treated with ω-3+ω-6, and (D) CCL2 −/− treated with ω-3. Treatment was daily administered by gavage for 3 months. Fatty acids analysis was performed and retinas were histologically examined. Three-month-old wild type mice were used for comparison purposes. Real-time PCR and Western blot were performed for retinal inflammatory mediators. Results: Increased EPA and decreased AA levels were observed in both blood and retinas in the treatment groups. The outer nuclear layer thickness was increased in groups C (45.0±3.9 µm) and D (62.8±4.9 µm), compared with groups B (65.6±3.0 µm) and A (71.1±4.2 µm), and in younger mice, it was 98.0±3.9 µm. A decrease in NF-κB expression was noted in the treatment groups. Interleukin (IL) 18 protein levels demonstrated a significant reduction in the ω-3-treated group only. Conclusion: Supplementation with ω-3+ω-6 or ω-3 alone (AA/EPA=1–1.5) suggests a protective mechanism in the CCL2 −/− animal model of dry AMD, with a more beneficial effect when ω-3 are used alone. Our findings indicated that inflammation is not the only determining factor; perhaps a regenerative process might be involved following administration of ω-3 fatty acids.